The Effectiveness Of Implementation Of The Bureaucracy Reform In Regional Government - Gusti Batara M.Nur, Cipta; Ginting, Henndy (GEMA EKONOMI, 2023)
The governor's regulation regarding the roadmap for bureaucratic reform that has been stipulated requires the regional secretariat of West Java province to carry out bureaucratic reform, so that it will affect the areas being reformed. The purpose of this study is to assess the effectiveness of bureaucratic reform at the regional secretariat of West Java province. Using descriptive quantitative research methods. The population in this study were CIVIL SERVANT at the regional secretariat of West Java province, with a sample of 373 employees. The data collection in this study was using a questionnaire. The results of the research are assessing the effectiveness of bureaucratic reform in 8 areas, namely Change Management, Organizational Arrangement, Management Arrangement, Strengthening Accountability, Strengthening Supervision, Structuring Legislation/Policy Deregulation, HR Management System, and Public Services. This study shows that Strengthening Supervision and Structuring Legislation/Policy Deregulation is proven still on process to be effective in bureaucratic reform policies at the West Java regional secretariat, meaning that further efforts are needed to achieve the long-term goals of bureaucratic reform. The implications of the research results are in the form of advanced policies related to bureaucratic reform and evaluating the implementation of the regional secretariat of West Java province